2019
DOI: 10.36380/jwpr.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dietary Medicinal Plants and algae in Laying Japanese Quails

Abstract: The current study was conducted to examine the influences of Sargassam cristafolium, Gracilaria pulvinata, Rhus coriaria, and Punica granatum peel dried powder in two levels (10 and 20gr/kg) of dietary on productive performance and some egg quality characteristics of laying Japanese quail. A total of 675 (49 days old) Japanese quail were randomly distributed into nine groups with three replicates of 25 birds in each. Results showed that egg weight, shell weight, albumen weight and shell thickness were not infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The effects of PPP on the egg production parameters are shown in Table 1 (67,68,69,70,71). Most studies revealed an improvement in the production parameters of layer hens due to feeding on pomegranate (72).…”
Section: Layersmentioning
confidence: 99%
“…The effects of PPP on the egg production parameters are shown in Table 1 (67,68,69,70,71). Most studies revealed an improvement in the production parameters of layer hens due to feeding on pomegranate (72).…”
Section: Layersmentioning
confidence: 99%
“…The gizzard is considered as the true stomach in the avian with bigger muscularity than proventriculus, which plays a major role in the grinding food to be further digested by the small intestine 7 . Medicinal plants become more popular in recent years to improve quail's productivity and lowering mortality rates 8 .…”
mentioning
confidence: 99%